1998
DOI: 10.1086/305712
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Distributions along the Horizontal Branch

Abstract: We report on HST/WFPC2 U,V and far-ultraviolet observations of two Galactic Globular Clusters (GGCs), NGC 6205 = M13 and NGC 6093 = M80. Both of these clusters have horizontal-branch (HB) tails that extend to the helium-burning main sequence, with the hottest stars reaching theoretical effective temperatures above 35,000 K. In both clusters, groups of stars are found to be separated by narrow gaps along the blue HB sequence. These gaps appear at similar locations in the color-magnitude diagrams of the two clus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
259
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(275 citation statements)
references
References 49 publications
16
259
0
Order By: Relevance
“…Carretta et al 2011a;Sbordone et al 2011;Milone et al 2012;Cassisi et al 2013). tail (Ferraro et al 1998), with the concentration of blue tail stars increasing toward the cluster centre (Brocato et al 1998). M 80 presents a typical halo-type orbit, with a short period and small size, never leaving the inner 3-4 kpc of the Galaxy (Dinescu et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Carretta et al 2011a;Sbordone et al 2011;Milone et al 2012;Cassisi et al 2013). tail (Ferraro et al 1998), with the concentration of blue tail stars increasing toward the cluster centre (Brocato et al 1998). M 80 presents a typical halo-type orbit, with a short period and small size, never leaving the inner 3-4 kpc of the Galaxy (Dinescu et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few of these gaps may merely be statistical fluctuations ), others could be real features, as they often show up at similar locations in different clusters. Of particular interest is the gap at T eff ' 11;000-12,000 K, labeled '' G1 '' by Ferraro et al (1998), which appears to coincide with a '' jump '' in Strömgren u-band luminosity first discovered in M13 by Grundahl, Vandenberg, & Andersen (1998). For stars cooler than $11,500 K, Grundahl et al found good agreement between the observed and theoretical BHB loci, but the hotter stars' u magnitudes were brighter than predictions by $0.4 mag.…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence of the presence of a BSS bimodal distribution (Ferraro et al 1997) was found in M 3 and was later on confirmed for other clusters: M 55 (Zaggia et al 1997); 47 Tuc (Ferraro et al 2001); Pal 13 (Clark et al 2004); NGC 6752 (Sabbi et al 2004); M 5 (Warren et al 2006); and M 62 (Beccari et al 2006), while in ω Cen the bimodality seems to be ruled out .…”
Section: Article Published By Edp Sciencesmentioning
confidence: 78%
“…We will refer to BSS of the first and second types as primordial and collisional BSS. Recent results show that both formation mechanisms could be at work in a given cluster (Ferraro et al 1997;Piotto et al 2004;Davies et al 2004;Mapelli et al 2004Mapelli et al , 2006.…”
Section: Introductionmentioning
confidence: 99%